Automated RFID based library management systems - Ansari, Moiz S.; Khatri, Naveed Ghani (2011)
RFID provides one of the best solutions for the identification of assets. RFID is a new generation which provides auto identification and data collection technique. RFID allows identification of tagged books, using radio frequency. RFID based Library Management System (LMS) will help us to increase the flow of transaction for a library. The proposed system of LMS is based on UHF RFID readers, along with the antennas at library entrance and on all other transactional points of the library. This work discusses elimination of transactional module from existing RFID based Library Management System